The conservation of native, lowland Indonesian Begonia species (Begoniaceae) in Bogor Botanic Gardens - HARTUTININGSIH M. SIREGAR (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Siregar HM.2017. The conservation of native, lowland Indonesian Begonia species (Begoniaceae) in Bogor Botanic Gardens. Biodiversitas 18: 326-333. Indonesia has a diversity of indigenous (i.e. wild type) Begonia species thathave never been artificially hybridized. They are usually situated in tropical rain forests, from the lowlands to the uplands (2400 m asl.). There are many Begonia species that have not yet been collected and conserved ex-situ.Hence exploration and conservation of this diversity needs to be exensively pursued. The conservation of lowland adapted Begonia has been carried out for the last ten years in the Bogor Botanic Gardens. The research reported here developed an inventoryof the Begonia collection held in the green house of the Bogor Botanic Gardens nursery. The method used was a study of the plant expedition database which contains collection lists, locality of their discovery and ecological data for the localities. Plant collection registration, acclimatization, propagation and collection care were documented. Bogor Botanic Gardens has conserved 124 collections of Begonia, made up of 93 indigenous species and 31 exotic species. The reported origins for the collection areas follows: Java (9 accessions), Sumatra (37 accessions), Kalimantan (5 accessions), Sulawesi (11 accessions), Maluku (15 accessions), Papua (4 accessions), Bali and West Nusa Tenggara (6 accessions ) and East Nusa Tenggara (6 accessions). These wild Begonia have prospects for development as new ornamental plants and also as genetic material to research the creation of new Begonia varieties through artifial hybridization.Key words: Begonia, Begoniaceae, Conservation, Bogor Botanic Gardens